2021
DOI: 10.3855/jidc.14243
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus disease-related knowledge, attitudes, and practices among the residents of Al-Jouf region in Saudi Arabia

Abstract: Introduction: Efforts have been made to contain COVID-19. Human behavior, affected by knowledge and perceptions, may influence the course of disease. Methodology: A structured questionnaire was used to collect data from 422 participants. It consisted of 28 questions in four sections; seven questions about sociodemographic characteristics of participants, 12 questions to estimate level of knowledge about COVID-19, six questions to evaluate attitudes toward disease, and three questions to assess practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“…26 Taken together, increasing the accessibility to materials provided by health care authorities, intensive training programs for all categories of the healthcare workers, rigorous attentive protocols, and a commitment to change behavior/practice, will significantly benefit the spread of the outbreaks. 24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“…In addition, although some studies found higher levels of perceived severity in study participants with little or no educational qualifications compared with highly educated individuals [ 47 , 48 ], other studies reported that people with lower levels of education more often considered themselves to be at a lower risk of becoming infected with COVID-19 [ 37 , 48 ]. Regarding protective behaviour against COVID-19, several studies found no differences by education level [ 20 , 44 , 49 51 ]. In contrast, other studies reported that individuals with lower levels of education were less likely to adhere to COVID-19 safety recommendations [ 39 41 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…On 27 December 2019, the coronavirus disease-19 (COVID-19), caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) in Wuhan, China, was discovered and spread to the rest of the world [ 1 ]. Clinical manifestations of COVID-19 range from severe pneumonia with respiratory distress (mostly in elderly people with underlying comorbidities) to mild clinical manifestations or asymptomatic carriage (mostly in children and young adults) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%